2000
DOI: 10.1021/ic991492n
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Chains Formed from Neutral, Triangular Gold Complexes Sandwiching TlI and AgI. Structures of {Ag([Au(μ-C2,N3-bzim)]3)2}BF4·CH2Cl2, {Tl([Au(μ-C2,N3-bzim)]3)2}PF6·0.5THF (bzim = 1-Benzylimidazolate), and {Tl([Au(μ-C(OEt)═NC6H4CH3)]3)2}PF6·THF, with MAu6 (M = Ag+

Abstract: It has been found that several trinuclear complexes of AuI interact with silver and thallium salts to intercalate Ag+ and Tl+ cations, thereby forming chains. The resulting sandwich clusters center the cations between the planar trinuclear moieties producing structures in which six AuI atoms interact with each cation in a distorted trigonal prismatic coordination. The resultant (B3AB3B3AB3)infinity pattern of metal atoms also shows short (approximately 3.0 A) aurophilic interactions between BAB molecular cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
80
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(92 citation statements)
references
References 62 publications
11
80
0
1
Order By: Relevance
“…However, equivalent and shorter metal–metal distances were described for the dinuclear complexes [AuAg{CH 3 im(CH 2 py)} 2 ](BF 4 ) 2 [CH 3 im(CH 2 py) = 1‐methyl‐3‐(2‐pyridinylmethyl)imidazole]20 and [(dpim) 3 AuAg](BF 4 ) 2 [dpim = 2‐(diphenylphosphanyl)‐1‐methylimidazole], respectively 21. Shorter distances were also found in the trinuclear complex [AuAg 2 {(pyCH 2 ) 2 im} 2 (NCCH 3 ) 2 ](BF 4 ) 3 [(pyCH 2 ) 2 im = 1,3‐bis(2‐pyridylmethyl)imidazole],22 in the tetranuclear cation [{(Ph 3 P)Au(μ‐mes)Ag(thz)} 2 ] 2+ ,23 in the clusters [Au 6 Ag{μ‐C 6 H 2 (CHMe 2 ) 3 } 6 ] + ,24 [Au 3 Ag(μ 3 ‐O)(PPh 2 py) 3 ] 2+ ,25 [Au 5 Ag 8 (μ‐dppm) 4 {1,2,3‐C 6 (C 6 H 5 ) 3 }(C≡CC 6 H 5 ) 7 ] 3+[26] and (Bu 4 N) 2 [Au(3,5‐C 6 F 3 Cl 2 ) 2 Ag 4 (CF 3 COO) 5 ],27,28 and in polymers such as [{Au(μ‐mes)AsPh 3 } 2 Ag](ClO 4 ),29 [AgAu(mtp) 2 ] (mtp = diphenylmethylenethiophosphinato),30 {[AuAg(Meimpy) 2 (L)](BF 4 ) 2 } n , {[AuAg(Meimpy) 2 (NO 3 )]NO 3 } n (Meimpy = methylimidazolepyridine; L = CH 3 CN, C 6 H 5 CN, C 6 H 5 CH 2 CN),31 [Au 2 Ag 2 (C 6 F 5 ) 4 (OCMe 2 ) 2 ] n ,32 [Au 2 Ag 2 (C 6 F 5 ) 4 (NCCH 3 ) 2 ] n ,33 or Ag([Au(μ‐C 2 ,N 3 ‐bzim)] 3 ) 2 · BF 4 · CH 2 Cl 2 ,34,35 [AuAg 4 (mes)(CF 3 CO 2 ) 4 (tht)] n , [AuAg 4 (mes)(CF 3 CF 2 CO 2 ) 4 (tht)] n , [AuAg 4 (mes)(CF 3 CF 2 CO 2 ) 4 (tht) 3 ] n , {[AuAg 4 (mes)(CF 3 CO 2 ) 4 (tht)(H 2 O)] · H 2 O · CH 2 Cl 2 } n ,17 [AuAg 3 (C 6 F 5 )(CF 3 CO 2 ) 3 (CH 2 PPh 3 )] n ,36 [AgAu(C 6 F 5 )(CF 3 CO 2 )(tht)] n , [Ag 2 Au(C 6 Cl 2 F 3 )(CF 3 CO 2 ) 2 (tht)] n , and [AgAu(C 6 Cl 5 )(CF 3 CO 2 )(tht)] n 18…”
Section: Resultsmentioning
confidence: 99%
“…However, equivalent and shorter metal–metal distances were described for the dinuclear complexes [AuAg{CH 3 im(CH 2 py)} 2 ](BF 4 ) 2 [CH 3 im(CH 2 py) = 1‐methyl‐3‐(2‐pyridinylmethyl)imidazole]20 and [(dpim) 3 AuAg](BF 4 ) 2 [dpim = 2‐(diphenylphosphanyl)‐1‐methylimidazole], respectively 21. Shorter distances were also found in the trinuclear complex [AuAg 2 {(pyCH 2 ) 2 im} 2 (NCCH 3 ) 2 ](BF 4 ) 3 [(pyCH 2 ) 2 im = 1,3‐bis(2‐pyridylmethyl)imidazole],22 in the tetranuclear cation [{(Ph 3 P)Au(μ‐mes)Ag(thz)} 2 ] 2+ ,23 in the clusters [Au 6 Ag{μ‐C 6 H 2 (CHMe 2 ) 3 } 6 ] + ,24 [Au 3 Ag(μ 3 ‐O)(PPh 2 py) 3 ] 2+ ,25 [Au 5 Ag 8 (μ‐dppm) 4 {1,2,3‐C 6 (C 6 H 5 ) 3 }(C≡CC 6 H 5 ) 7 ] 3+[26] and (Bu 4 N) 2 [Au(3,5‐C 6 F 3 Cl 2 ) 2 Ag 4 (CF 3 COO) 5 ],27,28 and in polymers such as [{Au(μ‐mes)AsPh 3 } 2 Ag](ClO 4 ),29 [AgAu(mtp) 2 ] (mtp = diphenylmethylenethiophosphinato),30 {[AuAg(Meimpy) 2 (L)](BF 4 ) 2 } n , {[AuAg(Meimpy) 2 (NO 3 )]NO 3 } n (Meimpy = methylimidazolepyridine; L = CH 3 CN, C 6 H 5 CN, C 6 H 5 CH 2 CN),31 [Au 2 Ag 2 (C 6 F 5 ) 4 (OCMe 2 ) 2 ] n ,32 [Au 2 Ag 2 (C 6 F 5 ) 4 (NCCH 3 ) 2 ] n ,33 or Ag([Au(μ‐C 2 ,N 3 ‐bzim)] 3 ) 2 · BF 4 · CH 2 Cl 2 ,34,35 [AuAg 4 (mes)(CF 3 CO 2 ) 4 (tht)] n , [AuAg 4 (mes)(CF 3 CF 2 CO 2 ) 4 (tht)] n , [AuAg 4 (mes)(CF 3 CF 2 CO 2 ) 4 (tht) 3 ] n , {[AuAg 4 (mes)(CF 3 CO 2 ) 4 (tht)(H 2 O)] · H 2 O · CH 2 Cl 2 } n ,17 [AuAg 3 (C 6 F 5 )(CF 3 CO 2 ) 3 (CH 2 PPh 3 )] n ,36 [AgAu(C 6 F 5 )(CF 3 CO 2 )(tht)] n , [Ag 2 Au(C 6 Cl 2 F 3 )(CF 3 CO 2 ) 2 (tht)] n , and [AgAu(C 6 Cl 5 )(CF 3 CO 2 )(tht)] n 18…”
Section: Resultsmentioning
confidence: 99%
“…Intermolecular aurophilic interactions have been shown to be highly sensitive to conditions such as temperature with several examples of gold(I) trimers displaying thermochromism 2. 5 The triazolate‐based trimer investigated by Coppens and Omary et al 2. displays a shift in emission wavelength upon cooling from approximately 725 nm at 280 K ( λ ex =280 nm) to 755 nm at 90 K. The shift in emission can be attributed to a reduction in intermolecular aurophilic interaction length from 3.42 Å at room temperature to 3.19 Å at 90 K. Time resolved photocrystallographic studies of the copper analogue have observed similar structural distortions in the excited state, confirming the temperature induced structural distortion is directly linked to the change in emission spectrum 6.…”
Section: Introductionmentioning
confidence: 99%
“…), which was characteristic of a Au I Ag I heterometallic interaction,11a, 12 in addition to the original, less‐intense phosphorescence at 693 nm. The same phosphorescence properties were also observed when EtOH and water were used as solvents.…”
Section: Resultsmentioning
confidence: 92%
“…Moreover, we have not yet observed any phosphorescence color changes upon exposure of [Au 3 Pz 3 ]/silica hex to other metal ions, such as Cu I , Ir I , Rh I , and Re I , owing to the selective interactions of Ag I to the trinuclear gold(I)–pyrazolate complex in the congested silicate nanochannels 11a. 12 The initial phosphorescence intensity and red emission could be recovered by using the same concentration of cetyltrimethylammonium chloride (CTAC) in CHCl 3 as AgOTf 11a. These observations indicated that the nanoscopic channel of hexagonal mesoporous silica played an essential role in the immobilization of the 1D columnar assembly of [Au 3 Pz 3 ] for the permeation of metal ions.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation